Concomitant NSAID use during antipsychotic treatment and risk of 2-year relapse – a population-based study of 16, 253 incident patients with schizophrenia. (23rd May 2016) - Köhler, Ole; Petersen, Liselotte; Benros, Michael Eriksen; Mors, Ole; Gasse, Christiane
ABSTRACT: Objective : Clinical trials have indicated antipsychotic effects of non-steroidal anti-inflammatory drugs (NSAIDs) among incident patients with schizophrenia. We aimed to study, in a population-based setting, whether concomitant use of NSAIDs or paracetamol, changed 2-year relapse risk for schizophrenia. Methods : We identified all incident patients with schizophrenia in Denmark diagnosed 1996–2012 initiating antipsychotic treatment within the year after diagnosis. We calculated concomitant treatment intervals for antipsychotic and NSAID or paracetamol use. Hazard rate ratios (HRR) were estimated using Cox regression adjusted for important covariates. Main outcome measures : 2-year relapse, i.e. (re)-hospitalizations with schizophrenia. Results : Among 16, 235 incident patients with schizophrenia using antipsychotics, 1480 (9.1%) used NSAIDs and 767 (4.7%) paracetamol. Concomitant use of NSAIDs was associated with an increased risk of schizophrenia relapse (HRR = 1.21; 95%-CI = 1.11-1.31), particularly associated with acetylsalicylic acid and diclofenac. Concomitant use of paracetamol was not associated with schizophrenia relapse (HRR = 0.97; 95%-CI = 0.87-1.08). Subgroup analyses showed that individuals with somatic comorbidity and NSAID use had an increased relapse-risk, except for individuals with a prior hospital diagnosis for musculoskeletal disease and NSAID use who had a decreased relapse-risk (HRR = 0.82; 95%-CI = 0.71-0.94). Conclusions : The increased relapse risk associated with concomitant NSAID use among incident patients with schizophrenia may indicate a potential impact of underlying somatic comorbidity.